Evaluation criteria and approval process of venture capital companies in Malaysia - Mohd Shariff, Mohd Noor; Hashim, Mohd Khairuddin; Mahajar, Abdul Jumaat; Ahmad, Sa'ari; Zakaria, Mustafa; Ahmad Fawzi, Dzulhilmi (2004)
In Malaysia, venture capital is beginning to be recognized as an important source offinancing for small and medium-sized enterprises (SMEs). Although this seemed to be the case, the review of the small business literature reveals that research efforts on venture capital firms in Malaysia remained limited both in terms offocus and scope. This study examines the evaluation criteria and approval process of venture capital companies in Malaysia. The study was based on the modest samples of 17 venture companies that are actively operating in Malaysia. By using a structured questionnaire developed from the literature, the data were gathered through face-to-face interviews with senior oficers of the selected companies. The findings on the evaluation criteria made by venture capital companies confirmed with the previous literatures that emphasized on the quality of the entrepreneur and management team, market potential of new business proposals and technology standard. The study also confirmed that various groups of venture capitalists have certain key and important criteria in evaluating the business proposals. Finally, a majority of the venture companies have a set of standard criteria of approving the investment proposal.